Tuning reductase activity in monoterpene indole alkaloid biosynthesis - Samuel C. Carr; Song Wu; Klaus Gase; Yoko Nakamura; Mohamed O. Kamileen; Maritta Kunert; Sarah Heinicke; Moonyoung Kang; Veit Grabe; Lorenzo Caputi; Sarah E. O’Connor (Proceedings of the National Academy of Sciences, 2026)
Monoterpene indole alkaloids encompass a diverse class of plant natural products. Many of these valuable compounds, including the anticancer medicines vinblastine and vincristine ( Catharanthus roseus ) and the antiaddiction treatment ibogaine ( Tabernanthe iboga ) utilize a common biosynthetic intermediate, 19 E -geissoschizine, which is produced by the medium-chain dehydrogenase/reductase geissoschizine synthase (GS). Herein, we report facilitator of geissoschizine synthase (FoGS), a protein that improves formation of 19 E -geissoschizine by acting in combination with GS. The identification of a FoGS ortholog that works with GS to produce 19 Z -geissoschizine shows how this protein also enables control over product stereochemistry. We demonstrate that FoGS and GS interact to form a stable heterodimer and through mutagenesis identify FoGS residues that contribute to the combined activity of FoGS and GS. This work highlights the involvement of proteins in metabolic pathways that, when assayed alone, appear nonessential, but nevertheless increase the efficiency or specificity of a given metabolic step.